Some Antiviral Mushrooms of Nepal - Adhikari, Mahesh Kumar (Nepal Journal of Science and Technology, 2020)
The present paper is a review based on published papers to highlight about some potential antiviral mushrooms, which are also found in Nepal. Nepalese mushrooms have not been yet analyzed and investigated so far for their antiviral properties except antioxidant and ACE-Inhibition sources on 62 Nepalese mushrooms as evidence-based complementary and alternative medicine. The published paper from abroad includes the species like: Calvatia gigantia, Cordyceps militaris, Cortinarius caperatus, Fomes fomentarius, Ganoderma lucidum, Grifola frondosa, Hericium erinaceus, Inonotus hispidus, Inonotus obliquus, Lentinula edodes, Omphalotus illudens, Ophiocordyceps sinensis, Phellinus ignarius, Pleurotus citrinopileatus, Pleurotus eryngii. Pleurotus ostreatus, Polyporus umbellatus, Russula delica. Schizophyllum commune, Scleroderma citrinum, Tremella sp. and Trametes versicolor, which are also found in the natural temperate (Schima – Castanopsis - Rhododrendron – Quercus) forests of Kathmandu valley. This paper may provide the researchers a glimpse to the aspects of experiment and lead to investigate on medicinal, antiviral and antibacterial properties of mushrooms found in Nepal. Gautam & Adhikari (2007) have screened Ophicordyceps sinensis for its chemical compound.